2014
DOI: 10.5194/bgd-11-901-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benthic biomass size spectra in shelf and deep-sea sediments

Abstract: The biomass distributions of marine benthic metazoans (meio-to macro-fauna, 1 µg-32 mg wet weight) across three contrasting sites were investigated to test the hypothesis that allometry can consistently explain observed trends in biomass spectra. Biomass (and abundance) size spectra were determined from observations made at the Faroe-Shetland Channel (FSC) in the Northeast Atlantic (water depth 1600 m), the Fladen Ground (FG) in the North Sea (150 m), and the hypoxic Oman Margin (OM) in the Arabian Sea (500 m)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The term e k1z reflects an increasingly higher cost for respiration (e.g., due to deficiency of oxygen and sediment consolidation) of moving (mixing) down the sediment column, which is consistent with the exponential decay of sediment porosity (p). Mortality is assumed to be controlled mainly by predation and dependent upon biomass (Kelly-Gerreyn et al, 2014). Predationinduced mortality is assumed to be highest at sediment-water interface and exhibits an exponential decay along depth due to respiration cost (thus the same k is used in the exponential function).…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term e k1z reflects an increasingly higher cost for respiration (e.g., due to deficiency of oxygen and sediment consolidation) of moving (mixing) down the sediment column, which is consistent with the exponential decay of sediment porosity (p). Mortality is assumed to be controlled mainly by predation and dependent upon biomass (Kelly-Gerreyn et al, 2014). Predationinduced mortality is assumed to be highest at sediment-water interface and exhibits an exponential decay along depth due to respiration cost (thus the same k is used in the exponential function).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Since then, numerous studies have confirmed a comparable importance of food quality in regulating the biomass and structure of benthic macrofaunal community (e.g., Herman et al, 1999;Kröncke, 2006;Reiss & Kröncke, 2005;Rodil et al, 2008;Venturini et al, 2011;Wieking & Kröncke, 2003. So far, only a few modeling attempts have been made to reveal a quantitative link between infaunal macrobenthos and sedimentary OC (e.g., Kelly-Gerreyn et al, 2014;Whearcroft et al, 1990), yet none has explicitly taken into account the impact of food quality, which is found to impose a critical control on macrobenthic community structure in shallow-water environments such as coastal waters and shelf seas (Lopez & Levinton, 1987). Unraveling such link would enable us to predict the variation of the biomass and community structure of infaunal macrobenthos in response to a change of food supply in terms of quantity and quality in any given environmental setting.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon food web models have been limited to steady state conditions because temporal data on model compartments and flux rates are not available Kelly-Gerreyn et al 2014). However, data on the changes in carbon stocks and process rates are available at Station M and often in high resolution due to innovative autonomous technology developments.…”
Section: Model Improvementsmentioning
confidence: 99%
“…A dynamic LIM developed using Station M time-series data and carbon flows in relation to changing POC flux, such as collected and analyzed in this study, would enable predictions of changes in the deep ocean benthic food web. An alternative modeling approach that utilizes allometry to study biomass distribution in marine benthic systems and effect of POC flux variation has also recently been developed (Kelly-Gerreyn et al 2014). The Station M time-series would be a useful tool to compare the allometric and LIM approaches.…”
Section: Model Improvementsmentioning
confidence: 99%
“…Large photographic surveys of the seabed have revealed substantially higher standing stocks of deep-sea megabenthos than corresponding trawl catch data (Morris et al 2014, Durden et al 2015a, thus the use of seabed photography to improve quantification of biomass is logical and of potentially substantial significance to our understanding of deep-sea ecology in general, and carbon budgets in particular. For example, consider the expectation that the distribution of biomass in marine communities may be constant across logarithmic size classes (Sheldon et al 1972), or increase continuously in logarithmic classes among the benthos (Bett 2013, Kelly-Gerreyn et al 2014. Consequently, a substantial fraction of standing stock carbon may be represented by the megabenthos that are currently grossly underestimated from trawl catch data.…”
Section: Introductionmentioning
confidence: 99%